Avaliação experimental de um sistema não linear para extração de energia através de vibrações utilizando material piezelétrico - Carvalho, Felipe Carmo [UNESP] (2014)
In order to meet the need for alternative energy sources to power autonomous microelectronic systems, studies have focused on the use of piezoelectric materials to transform energy derived from mechanical vibrations into electrical energy. Once the power delivered by the cantilever beams with piezoelectric materials are insufficient to power electronic devices autonomously, extraction techniques, conversion and energy storage was used to optimize the final accumulated energy. Considering that, this work aims at the optimization of an extractor system energy through vibrations using piezoelectric material, maximizing the power extracted and improving system performance. To this end, conditions of linearity and non-linearity in the mechanical system, as well as designed and tested converter circuits were analyzed. The best setup for electromechanical energy extraction, was used to feed an autonomous system. Two different power consumption-monitoring systems were designed to assess the limitation and potentialities of the proposed alternative for energy harvesting